The epidimiological aspects of the control for cronic drug-resistant tuberculosis patients - A. L. Khanin; S. A. Dolgikh (Бюллетень сибирской медицины, 2012)
The results of the dispensary control for 188 patients with drug-resistant tuberculosis having been analysed during 3—5 years; those patients hadn’t received the adequate chemical therapy: 50% — died because of growing more serious tuberculosis in the first 2 years of the control, 33% — the process became cronic, 7,4% — self-recovered, 9,6% — left for other places or for the prison hospitals. Some patients are known to infect with drug-resistant strains MBT nearly 1 500 people every year, thus keeping the circulation among town population DR/MBT as well as the high level of drug-resistant tuberculosis cases.